Idiosyncratic responses of aquatic and terrestrial insects to different levels of environmental integrity in riparian zones in a karst tropical dry forest region - Roque, Fabio O.; Correa, Elaine C.; Valente-Neto, Francisco; Stefan, Greici; Schulz, Gabriela; Souza, Paulo R. Barbosa; Motta, Caroline M.; Bavutti, Leticia L. Oliveira; Colzani, Emilio; Demetrio, Manoel F.; Escarpinati, Suzana C.; Silvestre, Rogerio; et al. (Wiley-Blackwell, 2017)
Decisions about biodiversity conservation depend on how different taxonomic groups respond to human-influenced environmental change. Here, we ask whether richness and composition of terrestrial (frugivorous butterflies and dung beetles) and aquatic insects (Plecoptera, Trichoptera, Ephemeroptera, Odonata and Coleoptera) change in a congruent manner across a gradient of riparian habitat degradation in a karst tropical dry forest region of Brazil, the Bodoquena Plateau. Our results showed incongruent ordination patterns based on the different taxa analysed. We found no correlation between richness and composition of the groups and environmental integrity. Incongruent responses among the taxonomic groups may be a consequence of high variability in ecological requirements among different taxa. Additionally, the effect of human disturbance on these taxonomic groups can be masked by the predominant presence of generalist species in tropical dry forests and by historical factors related to the adaptability of several species to changing ecosystems.
Keywords: human impact; macroinvertebrate; multi-taxa